A REVIEW ON A SECURITY MECHANISM IN CLOUD ENVIRONMENT - Kaur, Jaspreet; Kaler, Navdeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Cloud computing is a way to increase the capacity or add capabilities dynamically without investing in new infrastructure, training new personnel, or licensing new software. As information exchange plays an important role in today’s life, information security becomes more important. This paper is focused on the security issues of cloud computing and techniques to overcome the data security issue. Before analyzing the security issues, the definition of cloud computing and brief discussion to under cloud computing is presented. The various components that affect the security of the cloud and the problems faced by cloud service provider have been discussed in this paper.